Tumor necrosis factor reduces Plasmodium falciparum growth and activates calcium signaling in human malaria parasites - Cruz, Laura N.; Wu, Yang; Ulrich, Henning; Craig, Alister G.; Garcia, Célia R.S. (Biochimica et biophysica acta, 2016)
Plasmodium has a complex biology including the ability to interact with host signals modulating their function through cellular machinery. Tumor necrosis factor (TNF) elicits diverse cellular responses including effects in malarial pathology and increased infected erythrocyte cytoadherence. As TNF levels are raised during Plasmodium falciparum infection we have investigated whether it has an effect on the parasite asexual stage. Flow cytometry, spectrofluorimetric determinations, confocal microscopy and PCR real time quantifications were employed for characterizing TNF induced effects and membrane integrity verified by wheat germ agglutinin staining. TNF is able to decrease intracellular parasitemia, involving calcium as a second messenger of the pathway. Parasites incubated for 48h with TNF showed reduced erythrocyte invasion. Thus, TNF induced rises in intracellular calcium concentration, which were blocked by prior addition of the purinergic receptor agonists KN62 and A438079, or interfering with intra- or extracellular calcium release by thapsigargin or EGTA (ethylene glycol tetraacetic acid). Importantly, expression of PfPCNA1 which encodes the Plasmodium falciparum Proliferating-Cell Nuclear Antigen 1, decreased after P. falciparum treatment of TNF (tumor necrosis factor) or 6-Bnz cAMP (N6-benzoyladenosine-3′,5′-cyclic monophosphate sodium salt). This is potentially interesting data showing the relevance of calcium in downregulating a gene involved in cellular proliferation, triggered by TNF. The data show that Plasmodium may subvert the immunological system and use TNF for the control of its proliferation within the vertebrate host. •TNF is able to decrease parasitemia in P. falciparum‐infected RBCs.•TNF induced rises in intracellular calcium concentration, which were blocked by the purinergic receptor agonists KN62 and A438079.•Interfering with intra‐ or extracellular calcium release by thapsigargin or EGTA also block TNF‐induce calcium release in P. falciparum.•Expression of the P. falciparum Proliferating‐Cell Nuclear Antigen 1 (PfPCNA1) decreased after P. falciparum treatment with TNF or 6‐Bnz cAMP.•The data show that Plasmodium may subvert the immunological system and use TNF for the control of its proliferation within the vertebrate host.